2019
DOI: 10.1021/acs.jpclett.9b02168
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Engineering in Cs2(NaxAg1–x)BiCl6 Double Perovskite Nanocrystals

Abstract: Lead-free double perovskite materials, A 2 M(I)M′(III)X 6 , have recently attracted attention as environment-friendly alternatives to lead-based perovskites, APbX 3 , because of both rich fundamental science and potential applications. We report band gap tuning via alloying of Cs 2 AgBiCl 6 nanocrystals (NCs) with nontoxic, abundant Na. It results in a series of Cs 2 Na x Ag 1−x BiCl 6 (x = 0, 0.25, 0.5, 0.75, and 1) double perovskite NCs, leading to increase in optical band gap from 3.39 eV (x = 0) to 3.82 eV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 66 publications
12
93
0
1
Order By: Relevance
“…We speculate that such a lifetime retardation effect can be associated with the doping‐induced STEs state. The STEs state is dominating in the relatively slow exciton recombination process, and is a completely different system,22 which is consistent with the recent report that the STEs lifetime is independent of radiative or nonradiative recombination 26. Figure 2m depicts a plausible PL mechanism for the Ag + ‐doped Cs 2 NaBiCl 6 NCs.…”
Section: Figuresupporting
confidence: 87%
See 1 more Smart Citation
“…We speculate that such a lifetime retardation effect can be associated with the doping‐induced STEs state. The STEs state is dominating in the relatively slow exciton recombination process, and is a completely different system,22 which is consistent with the recent report that the STEs lifetime is independent of radiative or nonradiative recombination 26. Figure 2m depicts a plausible PL mechanism for the Ag + ‐doped Cs 2 NaBiCl 6 NCs.…”
Section: Figuresupporting
confidence: 87%
“…In contrast, for the Cs 2 AgBiCl 6 , the VBM consists mainly of Cl‐p, Ag‐d, and Bi‐s orbitals and the CBM consists mainly of Bi‐p, Cl‐p, and Ag‐s orbitals 15. As illustrated in the previous work,22 with doping Ag + ions in the Cs 2 NaBiCl 6 DP lattices, the orbitals of Ag + ions (Ag‐d and Ag‐s) involve into the formation of the VBM and CBM of the Cs 2 Ag x Na 1‐ x BiCl 6 , leading to the modification of electronic structures. As a result, the Ag + ‐doped Cs 2 NaBiCl 6 NCs display bright orange–red emission under the UV light (365 nm) excitation (the inset in Figure 2c).…”
Section: Figurementioning
confidence: 74%
“…The three different DFT functionals employed for the relaxation of the geometry of A 2 AgRhCl 6 were SCAN-rVV10 (Sun et al, 2015;Sun J. et al, 2016;Buda et al, 2017), PBE (Perdew et al, 1996) and PBEsol (Perdew et al, 2008). The reason for choosing three functionals is that we were interested in determining the extent to which the latter two functionals underestimate the bandgaps of the systems under investigation compared to SCAN-rVV10, since they generally underestimate the bandgap of halide single and double perovskites compared to both experiment and the computationally expensive GW and HSE06 (Volonakis et al, 2017;Lamba et al, 2019;Umadevi and Watson, 2019;Wang H.-C. et al, 2019). We note that the newly-proposed SCAN-rVV10 functional is one of the strongly constrained and appropriately normed metageneralized gradient approximation (meta-GGA) functionals that is considered to model well metallic, insulating and semiconducting materials (Sun et al, 2015;Sun J. et al, 2016;Buda et al, 2017).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Similarly, others (Yang et al, 2018) have observed that the bandgap of Cs 2 AgIn x Bi 1−x Cl 6 can be tuned from indirect (x = 0, 0.25, and 0.5) to direct (x = 0.75 and 0.9) by manipulating the percentage of doping, and that they exhibited 3 times greater absorption cross section, lower sub-bandgap trap states, and more than 5 times the photoluminescence quantum efficiency (PLQE) compared to those observed for indirect bandgap nanocrystals such as Cs 2 AgBiCl 6 . Bandgap tuning by alloying of Cs 2 AgBiCl 6 nanocrystals resulted in a series of Cs 2 Na x Ag 1−x BiCl 6 (x = 0, 0.25, 0.5, 0.75, and 1) double perovskite nanocrystals that showed an increase in optical bandgap from 3.39 eV (x = 0) to 3.82 eV (x = 1) and a 30-fold increment in weak photoluminescence (Lamba et al, 2019). Other materials generated by replacing the B ′ -site species in A 2 BB ′ X 6 with transition metals such as Mn 3+ (Locardi et al, 2018;Nandha and Nag, 2018;, Cr 3+ (Zhao et al, 2019), etc., via partial or heavy doping play a significant role in the discovery of innovative halide double perovskite materials for optoelectronics (Jain et al, 2017;Bartel et al, 2019;Cai et al, 2019;Li and Yang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that band gap engineering can also be performed for low‐dimensional HDPs. For example, the band gap of Cs 2 AgBiCl 6 NCs is enlarged through alloying with Na cations [66] . If the content of Na cations increases from 0 to 1, the band gap rises from 3.39 to 3.82 eV, possibly resulting from a reduction of the Ag contribution near the VBM upon incorporation of Na ions.…”
Section: Preparation Methods For Hdpsmentioning
confidence: 99%